2018
DOI: 10.1038/mi.2017.98
|View full text |Cite
|
Sign up to set email alerts
|

Absence of specific alternatively spliced exon of CD44 in macrophages prevents colitis

Abstract: CD44 is a transmembrane molecule appearing in numerous isoforms generated by insertions of alternatively spliced variant exons (CD44v) and having various binding partners. CD44v7 on T cells was proposed to promote colitis by preventing T-cell apoptosis. Here we demonstrate that Cd44v7-deficient T cells - like Cd44 wild-type (Cd44) T cells - provoked disease in two different colitis models: the model induced by CD4CD45RB T-cell transfer into Rag2-deficient mice and a new model based on ovalbumin (OVA)-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Moreover, high levels of OPN have been found in cerebrospinal fluid and serum of cancer patients [46] and it is considered a possible target for cancer therapy [23]. It is to be noted that the role in inflammation of OPN is possibly mediated by CD44 isoforms [47,48], suggesting that a specific inflammatory pathway could be the target of BSH or BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of OPN have been found in cerebrospinal fluid and serum of cancer patients [46] and it is considered a possible target for cancer therapy [23]. It is to be noted that the role in inflammation of OPN is possibly mediated by CD44 isoforms [47,48], suggesting that a specific inflammatory pathway could be the target of BSH or BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al revealed that CD44 expression inhibited ferroptosis in cancer cells in an OTUB1-dependent manner 34 . It has been suggested that the absence of specific CD44 variable splice exons in macrophages prevents CD 35 . It remains to be investigated whether CD44 , a ferroptosis inhibitor, could exacerbate CD by reducing ferroptosis in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that soluble caveolin-1-Ig inhibits T cell proliferation and cytokine production in response to recall antigen or alloantigen-presenting cells (APC), and in combination with our study, CAV1 was negatively correlated with memory resting CD4 + T cells, suggesting that CAV1 may be involved in CD progression by inhibiting T cell proliferation 52 . CD44 has been shown to block apoptosis of CD4 + T cells that activate colitis 35 , 53 . The inhibitor of ferroptosis, CD44 , was negatively correlated with memory resting CD4 + T cells in the present study, which may suggest that CD44 exacerbates CD in the intestine by inhibiting apoptosis or ferroptosis of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD44v7 deletion in macrophages of recipient mice might link to the down‐regulation of STAT3‐activating and forkhead box P3 (Foxp3)‐counteracting IL‐6, which would cause decreased numbers of phospho‐STAT3‐containing lymphocytes as well as elevated counts of Foxp3 + T‐cells in the gut (Figure 5A). 86 TL1A as well as its functional receptor (death‐domain receptor 3, DR3) have been considered as the key members of TNF/tumour necrosis factor receptor superfamilies of proteins. Once APC‐derived TL1A is bound to the lymphocytic DR3, TL1A–DR3 interaction exerts pleiotropic effects on different adaptive immune cells, including Treg and helper T cells, to influence cell proliferation, maintenance and differentiation 87,88 .…”
Section: How As Events Participate In the Pathogenesis Of Ibd?mentioning
confidence: 99%